Contributing Factors of Employee Performance - Purnamasari, Anggun; Millah, Alimul; Kartono, Kartono (IJBLE Scientific Publications Community Inc., 2024)
The purpose of this study is to examine how training and career development affect employee performance. Quantitative approaches are employed in this study. using methods for gathering data such as interviews and questionnaires. The study included 67 workers from the Director General of Sea Transportation as respondents. Multiple linear regression is the analytical technique employed, and the regression coefficient values are y =6,704+0.467x1 + 0.746x2. The research hypothesis test results indicate that employee performance of Director General of Sea Transportation is influenced by training and career development either in part or entirely at once